2021
DOI: 10.1080/19475705.2021.1955754
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the rockburst proneness of red sandstone with prefabricated boreholes: an experimental study from the energy storage perspective

Abstract: To reveal the function of drilling pressure relief (DPR) in preventing rockbursts from the energy storage perspective, we investigated the rockburst proneness of red sandstone with different number and arrangement of prefabricated borehole via uniaxial compression tests. The experimental result revealed the failure intensity characteristics of specimen can be quantitatively described using the peak-strength strain energy storage index (PESI). The PESI of red sandstone specimens with boreholes decreased by 23.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Liu 16 investigated the effects of coal body strength and unloading pressure relief borehole diameter on stress, the plastic zone, and permeability and gas distribution and concluded that the extent of the pressure relief zone, plastic zone, and permeability enhancement zone around the borehole in soft coal is significantly larger than that in hard rock. He 17 studied the role of pressure relief drilling in preventing impact ground pressure from the energy point of view and derived a new method for quantitatively evaluating the propensity of rock impacts after the DPR, which elucidated the effectiveness of the DPR in reducing the probability of rock burst occurrence. Lin 18 investigated the relationship between the destructive strength and the magnitude of horizontal stress and rock mass of a specific rock formation during unloading pressure relief of a borehole and concluded that the linear fracture initiation criterion can accurately calculate the destructive strength of coal rock.…”
Section: Introductionmentioning
confidence: 99%
“…Liu 16 investigated the effects of coal body strength and unloading pressure relief borehole diameter on stress, the plastic zone, and permeability and gas distribution and concluded that the extent of the pressure relief zone, plastic zone, and permeability enhancement zone around the borehole in soft coal is significantly larger than that in hard rock. He 17 studied the role of pressure relief drilling in preventing impact ground pressure from the energy point of view and derived a new method for quantitatively evaluating the propensity of rock impacts after the DPR, which elucidated the effectiveness of the DPR in reducing the probability of rock burst occurrence. Lin 18 investigated the relationship between the destructive strength and the magnitude of horizontal stress and rock mass of a specific rock formation during unloading pressure relief of a borehole and concluded that the linear fracture initiation criterion can accurately calculate the destructive strength of coal rock.…”
Section: Introductionmentioning
confidence: 99%
“…investigated the degree of influence of red sandstone specimen shape and rock material on rockburst sensitivity, and it was found that cubic specimens exhibited stronger rockburst sensitivity than cylindrical specimens. The rockburst characteristics of red sandstone with different arrangements of prefabricated holes were investigated by uniaxial compression tests, and it was found that the rockburst effect of red sandstone containing prefabricated holes was weaker than that of intact specimens (He et al, 2021). It was found that water gushing is highly likely to occur within the broken enclosure section, and the permeability and porosity of the enclosure increases with time due to the granular structure of the broken enclosure that easily forms water-conducting channels (Ma et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%